The Scheme of Stress Detecting Tools by Using HIR333, GSR and DS18B20 Censors Based On Microcontroller Atmega 8 - Tamba, Takdir (Talenta Publisher, 2019)
A human stress detector has been designed with the physiological parameters of stress. Stress is a common respond to the demands of the body. There is a necessity for self adjustment, thus it causes disturbance in body’s equilibrium. Nowadays, stress is not only experienced by the elders, but also young people. Stress also affects the condition of the body. When someone is stressed, the body will hold integrated reactions against the stressors. These reactions include the increasing heart rate, fast breathing, and cold sweating. The detector works on the condition of the body by using a GSR sensor to determine the conductivity of the skin, HIR333 to detect changes in heart and body temperature DS18B20, which then compared with the specified parameters.